Quo Vadis Constitutional Complaint in Indonesia: Authority and Discretion of Constitutional Judges/Quo Vadis Constitusional Complaint di Indonesia: Antara Kewenangan dan Diskresi Hakim Konstitusi - Mahfiana, Layyin; Lisma, Lisma (Fakultas Syariah, 2021)
AbstractThe guarantee of citizens' constitutional rights is one of the conditions for realizing an excellent legal state. However, several studies show that there is no precise mechanism for filing constitutional complaints. Although since 2003, a Constitutional Court has been established. This article aims to describe the problems of filing a constitutional complaint in Indonesia. This article is based on doctrinal legal research with a statutory and conceptual approach. The results of this study indicate that there is no regulation that authorizes the handling of constitutional complaint cases to the Constitutional Court. Judges of the Constitutional Court are rigid in examining cases under their authority and have never exercised discretion over them. This condition has the potential to ignore the constitutional rights of citizens. So there is a need for an amendment to the 1945 Constitution and a revision to the Constitutional Court Law. However, this change requires political will from the authorities.Keywords: constitusional complaint; constitutional court; discretion.Abstrak Jaminan hak konstitusi warga negara merupakan salah satu syarat terwujudnya negara hukum yang baik. Namun, sejumlah riset menunjukkan bahwa belum ada mekanisme yang jelas pengajuan constitutional complain. Meskipun sejak tahun 2003 telah dibentuk Mahkamah Konsititusi. Artikel ini bertujuan mendeskripsikan problematika pengajuan constitutional complain di Indonesia. Artikel ini berdasarkan penelitian hukum doktrinal dengan pendekatan peraturan perundang-undangan dan pendekatan konseptual. Hasil penelitian ini menunjukkan bahwa belum ada regulasi yang memberikan kewenangan penanganan perkara constitutional complaint kepada Mahkamah Konsitusi. Hakim Mahkamah Konstitusi rigid dalam memeriksa perkara yang menjadi kewenangannya dan tidak pernah melakukan diskresi terhadapnya. Kondisi ini berpotensi mengabaikan hak-hak konstitusi warga negara. Sehingga perlu adanya amandemen Undang-Undang Dasar 1945 dan revisi terhadap Undang-Undang Mahkamah Konstitusi. Namun, perubahan ini membutuhkan political will dari penguasa.Kata Kunci: constitutional complaint; mahkamah konstitusi; diskresi.